(untitled) (Research Announcements "Heritage BG", 2025)
The national legislation defines the parameters for the preservation and protection of cultural heritage in Bulgaria, including cultural values with the category ‘of local importance’. Since 2018, local authorities have had the responsibility to implement policy in this sector, which proves to be challenging for small municipalities in financial and expert terms. Today, the composition of the cultural monuments declared in the 1960s and 1970s is not well-known to municipal administrations; in many cases, local communities do not recognise them as ‘their’ heritage. Taking the case of the municipality of Balchik, the paper discusses how many of these monuments or immovable cultural values of local importance are now forgotten and/or ‘do not exist’, or are objects of interest for the purpose of developing cultural tourism. References: „Analiz na bulgarskata normativna ramka v oblastta na nematerialnoto kulurno nasledstvo spriamo mezhdunarodnite dokumenti v oblastta na nematerialnoto kulurno nasledstvo s vkliucheni preporaki.“, 2019. Available at: https://www.unesco-centerbg.org/wp-new/wp-content/uploads/2019/11/D0%B0%D0%BD%D0%B0%D0%BB%D0%B8%D0%B7-%D0%942.pdf (30.05.2023). Аlexieva, Bokova 2013: Аlexieva, Sonya, Bokova, Irena. Turizam i kulturno nasledstvo. Sofia: NBU. Bobcheva 1974: Bobcheva, Lyubka. Arheologicheska karta na Tolbuhinski okrag. Sofia. Bokova 2012: Bokova, Irena (ed.). Godishnik na departament „Antropologiya“: Kulturni nasledstva – politicheski zalozi i rekonstruirane na teritorii. Sofia: NBU. Doncheva-Petkova, Vitliyanov, Encheva 2004: Doncheva-Petkova, Lyudmila, Stoyan Vitlyanov, Radostina Encheva. Razkopki na halma „Dzhenni bair“. – Arheologicheski otkritiya i razkopki prez 2003 g. Manolova-Voykova 2015: Manolova-Voykova, Maria. Vnosna keramika ot selishteto varhu halma „Dzhenni Bair“ v gr. Balchik. V: Sbornik Dobrudzha. 30, 411 – 436. Melikoff 1999: Melikoff, Irene. Razmisli po problema bektashi-alevi. V: Islyam i kultura (sast. Galina Lozanova i Lyubomir Mikov]. Sofia, 11 – 24. Naredba № 3 ot 10.07.2019 g. na Ministerstvo na kulturata za reda za identifitsirane, deklarirane, predostavyane na statut i za opredelyane na kategoriyata na nedvizhimite kulturni tsennosti, za dostapa i podlezhashtite na vpisvane obstoyatelstva v natsionalniya publichen registar na nedvizhimite kulturni tsennosti. Posl. dop. v Darzhaven vestnik, 2021 g., br. 9. Natsionalna strategiya za regionalno razvitie na Republika Balgariya za perioda 2012-2022 g., available at: https://www.strategy.bg/StrategicDocuments/View.aspx?Id=772 [Accessed: 30 May 2023 g.]. Parusheva 2009: Parusheva, Tanya. Kulturniyat turizam: alternativa za globalizatsiya, Sofia: Izdatelstvo „Avangard Prima“. Radionova 1994: Radionova Diana. Teketo na Ak yazala baba pri s. Obrochishte, Balchishko. – Dobrudzha, 11(1), 61 – 75. Santova 2014: Santova, Mila. Da ulovish neulovimoto. Nematerialno kulturno nasledstvo, Sofia: Akademichno izdatelstvo „Prof. Marin Drinov“, 2014. Simeonova 2022: Simeonova, Irina. Rabotna sreshta na ekspertnata obshtnost v sferata na opazvaneto na nedvizhimoto kulturno nasledstvo se sastoya dnes. Available at: https://www.bta.bg/bg/news/lik/313981-rabotna-sreshta-na-ekspertnata-obshtnost-v-sferata-na-opazvaneto-na-nedvizhimoto [Accessed: 30 May 2023 g.]. Tablitsa na adresno registriranite po postoyanen i po nastoyasht adres litsa oblast DOBRICH, obshtina BALCHIK. Available at: https://www.grao.bg/tna/t41nm-15-09-2022_2.txt?fbclid=IwAR3CB1yky2xEj2z1-Tsu-TND0OmR8QsO-In7rwGUoIjlieVDGbZRggYmK5g [Accessed: 30 May 2023 g.]. Zakon za kulturnoto nasledstvo, 2009 g. Posl. izm. v Darzhaven vestnik, 2021 g., br. 17. Fischer 2000: Fischer, Frank. Citizens, Experts and the Environment: The Politics of Local Knowledge. Duke: Duke University Press. Rodenberg, Hulst 2012: Rodenberg, Jeroen, Rudie Hulst. Governance of Heritage. Discourses and Power in Heritage Policy Networks. Available at: https://www.academia.edu/4252062/Governance_of_heritage.Discourses_and_power_in_heritage_policy_networks.-_Jeroen_Rodenberg_and_Rudie_Hulst (30.05.2023) Schofield 2014: Schofield, John (ed.). Who Needs Experts? Counter-mapping Cultural Heritage. Farnham: Ashgate Publishing. Schofield, Szymanski 2010: Schofield, John, Rosy Szymanski (eds). Local Heritage, Global Context. Cultural Perspective on Sense of Place. London: Routledge. Vladimirov 2022: Vladimirov, Zhelyu. Assessment of Cultural Heritage in the Town of Shumen by the Locals and Intentions to Contribute to its Development. – Research Announcements Bulletin ‘Heritage BG’, ed. Emmanuel Moutafov, No 2, 5 – 13.